Hydroxysafflor yellow A inhibits epithelial- mesenchymal transition in hepatocellular carcinoma cell line Huh7 - WU Na, WANG Dong, LI Jing-min, BAI Xian-yong (Jichu yixue yu linchuang, 2021)
Objective To investigate the effect of hydroxysafflor yellow A (HSYA) on the migration and invasion in Huh7 cells, and to explore whether HSYA affects the epithelial-mesenchymal transition (EMT) of liver cancer in vitro and in vivo. Methods Human Huh7 cells were cultured in and divided into control group, 80 and 160 μmol/L HSYA experimental groups and treated for 24 h respectively. Wound healing and Transwell assay were used to evaluate the migration and invasion of HCC cells. Western blot analysis was used to detect the expression of vimentin and E-cadherin. To establish a model of Huh7 nude mice with subcutaneous xenograft, the morphology of transplanted tumor and liver tissues in nude mice were observed under microscopy with H/E staining. The expression of TGF-β1, vimentin and E-cadherin in tumor tissues was detected by immuno-histochemistry. Results Compared with the control group, cell migration and invasion of HSYA experimental group were significantly decreased, E-cadherin expression was increased, and vimentin expression was decreased(P＜0.05). Compared with the transplantation group, there was no tumor cell metastasis and tumor cell necrosis been found in the HSYA experimental group (2.25 mg/kg), expression of E-cadherin was increased and expression of vimentin as well as TGF-β1 was decreased(P＜0.05). Conclusions HSYA inhibits migration and invasion of HCC cells through inhibiting the occurrence of EMT.